1969
DOI: 10.2466/pr0.1969.25.1.235
|View full text |Cite
|
Sign up to set email alerts
|

Race, Sex, Ordinal Position of Birth, and Self-Disclosure in High School Students

Abstract: The Jourard and Lasakow (1958) Self-disclosure Questionnaire was administered to 120 high school students in order to examine relationships of birth order, race, and sex to self-disclosure. Results indicated that later borns disclosed more than firstborns, whites disclosed more than Negroes, and mother was the favorite target person. Further, firstborn Negroes disclosed less than any other group, females disclosed most to mother and female friend while males disclosed least to female friend, firstborns disclos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
21
0

Year Published

1978
1978
1987
1987

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(24 citation statements)
references
References 2 publications
3
21
0
Order By: Relevance
“…Thus, several studies have found that females disclose more than males and that some ethnic minorities, specifically Black, Puerto Rican, and Mexican American, disclose less than Anglo-Americans. Other studies, however, have reported no difference in amount of disclosure between Blacks and Anglos (17) and between genders (8,9,10).…”
Section: A Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…Thus, several studies have found that females disclose more than males and that some ethnic minorities, specifically Black, Puerto Rican, and Mexican American, disclose less than Anglo-Americans. Other studies, however, have reported no difference in amount of disclosure between Blacks and Anglos (17) and between genders (8,9,10).…”
Section: A Introductionmentioning
confidence: 88%
“…Theoretically, the individual who never discloses or the individual who discloses a great amount indiscrimintely may be perceived by others as maladjusted (19). Others have proposed that amount of self-disclosure is dependent on the individual's personality (5,8,9), gender (13,14,20,21), and ethnicity (21,32). Thus, several studies have found that females disclose more than males and that some ethnic minorities, specifically Black, Puerto Rican, and Mexican American, disclose less than Anglo-Americans.…”
Section: A Introductionmentioning
confidence: 93%
“…Specifically, Diamond and Hellcamp (1969), Woeken et al (1973), and Littlefield (1974) all found that whites tend to disclose at higher rates than blacks. The only study to find no significant differences in self-disclosure between blacks and whites is Jaffee and Polansky's (1962) study of lower-class adolescents showing delinquent trends.…”
mentioning
confidence: 95%
“…Finally, Ting-Toomey (1984) found ethnic (black/white) differences in conflict management styles. Research on ethnic differences in languages (e.g., Folb, 1982); nonverbal patterns (e.g., Johnson, 1972), self-disclosure (e.g., Diamond and Hellcamp, 1969), interrogation (e.g., Shuter, 1982), and communicator style/ attraction (e.g., suggests the following hypothesis:…”
mentioning
confidence: 98%
“…In many studies, however, differential disclosure levels have been reported for men and women and for members of minority groups. For example, it has been reported in several studies that women self-disclose more than do men (Hood & Back, 1971;Jourard & Landsman, 1960;Jourard & Lasakow, 1958;Pederson & Breglio, 1968) and that disclosure among Black, Puerto Rican, and Mexican-American ethnic minorities is significantly less than among AngloAmericans (Levine & France, 1981;Dimond & Hellkamp, 1969;Jourard & Lasakow, 1958;Littlefield, 1969). Conversely, some researchers have reported-no difference in disclosure patterns between lower socioeconomic class Blacks and Whites (Jaffee & Polansky, 1962) and between the sexes (Dimond & Hellkamp, 1969;Doster & Strickland, 1969).…”
mentioning
confidence: 99%